Student's Statistical Literacy skills Based on the Reflective and Impulsive Cognitive Styles - Masfingatin, Titin; Suprapto, Edy (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
This study aimed to describe students' statistical literacy skills based on their reflective-impulsive cognitive style. This study employed descriptive exploratory research with the qualitative approach. The data collecting techniques used were tests, interviews, and field notes. The data analysis techniques employed were data reduction, data presentation, and drawing conclusions. This study discovered that students’ reflective and impulsive cognitive styles influence their statistical literacy skills such as the ability to construct or interpret information or statistical data, understand statistical concepts, and represent the statistical data in a different form. Students with the reflective cognitive style were different from students with the impulsive cognitive style on statistical literacy skills, especially in evaluating statistical information or arguments. Students with the reflective cognitive style tended to be more critical in evaluating statistical information or arguments by providing arguments based on the results of analytical calculations. Students with the impulsive cognitive style used analytical processes in drawing statistical conclusions. Students with the impulsive cognitive style lacked cognitive maturity and tended to use processes holistically rather than analytically in drawing statistical conclusions.